Characterisation of the complete mitochondrial genome of Lucanus chengyuani (Coleoptera: Lucanidae). Issue 2 (3rd July 2019) - Wang, Liang-Jong; Huang, Jen-Pan; Shiao, Shiuh-Feng; Ko, Hsin-Ping; Sung, Chia-Hsuan
Abstract: We sequenced and assembled the complete mitochondrial genome of Lucanus chengyuani, from the Alishan, Chiayi County, Taiwan. The length of the complete mitogenome of L. chengyuani is 16, 926 bp and the mitogenome contains 13 protein-coding, 22 tRNA, and 2 rDNA genes. Nucleotide compositions of the whole mitogenome of L. chengyuani are 38.37% for A, 27.96% for T, 23.03% for C, and 10.637% for G. The AT and GC skewness of mitogenome sequence are 0.157 and -0.368, showing the A-skew and C-skew. The reconstructed phylogenetic relationships of 9 Lucanidae species based on 13 mitochondrial protein-coding genes are highly supported. The clade including Neolucanus maximus and Odontolabis cuvera is sister to the rest of the stag beetle clades, which contains L. chengyuani and L. mazama . Mitogenomic data from this study will provide useful information for further studies for the population genetics, speciation, biogeography, and conservation of L. chengyuani in the future.